PENGARUH PRODUK DOMESTIK BRUTO, JUMLAH UANG BEREDAR, INFLASI DAN BI RATE TERHADAP INDEKS HARGA SAHAM GABUNGAN DI INDONESIA PERIODE 2007 - 2013 - Dodi Arif (Universitas Gunadarma, 2015)
The capital market is an alternative investment that can provide the return on investment income and income shares of other investment securities that are traded in the stock market. To obtain the optimal stock returns in accordance with the risk that it contains, an investor should also know the actual stock price index is the index number of prices of stocks that have been compiled and calculated so as to produce a trend of stock price changes. By knowing the stock price index, investors can determine the condition of the capital markets in general. In capital markets, changes in stock prices are influenced by factors external systematic risk as the Gross Domestic Product (GDP), the money supply (M2), the level of inflation, SBI, and others. By using multiple linear regression techniques will be the factors that affect the bersiko external systematic changes in stock prices in Indonesia during the period 2007 to 2013. The results of the analysis carried out will be seen how big factors that will affect the systematic risk of the stock price in Indonesia. Keywords: Risk, Stock price.JUB, GDP, BI Rate